(untitled) (Sains Humanika, 2017)
The aim of this study was to find out the impact of earnings management on dividend policy of oil and gas companies listed at the Karachi stock exchange. The study uses annual data of oil and gas companies for the period from 2008 to 2015. The dependent and independent variables are dividend policy and earnings management and the three control variables are leverage, return on equity and firm size. Modified cross sectional Jones model (1995) was used for calculating discretionary accruals which has been used as proxy for earnings management whereas measurement of dividend policy has been proxy by dividend payout. The findings from regression analysis indicate that earnings management has insignificant relationship with dividend policy of selected firms in Pakistan. Financial crisis in the world and economic decline period are the main reasons of this relationship. In the decline period the firms try to increase manipulation in earnings as a result the company starts reducing dividend payments. It is concluded that there are some other factors that may influence the pattern of dividend payment in the firms.